Where have all the crop phenotypes gone? - Dani Zamir (PLoS Biology, 2013)
In crop genetics and breeding research, phenotypic data are collected for each plant genotype, often in multiple locations and field conditions, in search of the genomic regions that confer improved traits. But what is happening to all of these phenotypic data? Currently, virtually none of the data generated from the hundreds of phenotypic studies conducted each year are being made publically available as raw data; thus there is little we can learn from past experience when making decisions about how to breed better crops for the future. This ongoing loss of phenotypic information, particularly about crop productivity, must be stopped if we are to meet the considerable challenge of increasing food production sufficiently to meet the needs of a growing world population. Here I present a road map for developing and implementing an information network to share data on crop plant phenotypes.